Optimalisasi Kerja Karyawan Sistesis Coffee - Lisa Sulistiyowati; Nurhalimah Nurhalimah; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Journal of Management and Creative Business, 2023)
The purpose of the results of this visit is to find out how to optimize employee work and the level of satisfaction with employee gai.the method used is using Descriptive and Observative methods, using direct interviews, documentation, literature surveys, websites, and written sources both in print and electronic media to clarify the results of this visit. The interview was conducted with the person in charge of Sintesis Coffee who had obtained permission from the owner. This activity is carried out to find out how the performance of employees is in accordance with the compensation they get. From the results of the visit obtained salary data and the level of satisfaction with employee salaries, it is known that synthesis coffee has 4 employees and employee salary data is of course in accordance with the statement that the compensation is below the Karawang UMR, this is adjusted to the income generated from sales which on average is in the range of 15 - 20 million. and also obtained the level of employee satisfaction with the salary earned, quite satisfied to be the level for all employees. the results of our observations can be concluded that employee compensation is very influential on work optimization, both cash and non-cash compensation. Optimizing employee work is very important to make employees more able to explore knowledge and skills in developing a business. Efforts to optimize employee work can improve the quality of service to consumers and also provide evidence that human resource development certainly has a positive influence on the performance of coffee shop employees.